Mineralization of autochthonous particulate organic carbon is a fast channelof organic matter turnover in Germany's largest drinking water reservoir - Dordoni, Marlene; Seewald, Michael; Rinke, Karsten; Friese, Kurt; van Geldern, Robert; Schmidmeier, Jakob; Barth, Johannes (Biogeosciences, 2022)
Turnover of organic matter (OM) is an essential ecological function in inland water bodies and relevant for water quality especially for the potential of dissolved organic carbon (DOC) removal as well as due to emissions of CO2. We investigated various sources of OM including DOC, autochthonous particulate organic carbon (allo-POC), allochthonous particulate organic carbon (allo-POC), and sedimentary matter (SED) in a temperate drinking water reservoir (Rappbode Reservoir, Germany) with respect to carbon isotope ratios and concentration dynamics. For this purpose, we focused on the metalimnion and the hypolimnion, where respiratory turnover is expected to be dominant and hardly disturbed by atmospheric exchange. The observation period of nine months covered a complete stratification period of the water body. Dissolved inorganic carbon (DIC) concentrations and its isotopes (delta C-13(DIC)) were considered together with isotope data of DOC and POC (delta C-13(DOC) and delta C-13(POC)) as input parameters for mass balances. DIC concentrations ranged between 0.30 and 0.53 mmol L-1 , while delta C-13(DIC) values were between -15.1 and -7.2 parts per thousand versus the VPDB (Vienna PeeDee Belemnite) standard. Values of delta(13)C(DOC )and delta C-13(auto-POC) ranged between -28.8 and -27.6 parts per thousand and between -35.2 and -26.8 parts per thousand, respectively. Isotope compositions of sedimentary material and allochthonous POC were inferred from the literature with average values of delta C-13(SED) = -30.7 parts per thousand, and delta C-13(allo-POC) = -31.8 parts per thousand. Comparison of DIC concentration gains and stable isotope mass balances showed that autochthonous POC from primary producers was the main contributor to DIC increases, while contributions from DOC, ExtPOC and SED played a minor role. OM turnover rates, i.e. the conversion of organic carbon towards DIC, calculated with our isotope approach were within the range for oligotrophic water bodies (0.01 to 1.3 mu mol L(-1 )d(-1)). Some higher values in the metalimnion are likely due the availability of settling POC from the photic zone. Samples from a Metalimnetic Oxygen Minimum (MOM) showed a clear dominance of respiration over photosynthesis through bacterial degradation of autochthonous POC. These high turnover rates further highlight a close link with planktonic biological assemblages. Our work shows that respiration in temperate lentic water bodies largely depends on autochthonous POC production as a major carbon source
CRIS-Team WoS Importer:2022-12-09